Benthic fish blood as a biomarker for recent exposure to mercury - Furlan, Natalia; Quinaglia, Gilson A.; Esteves, Katharina E.; Osti, Joao A. S. [UNESP]; Lamparelli, Marta C. (Asoc Espan Limnol-mislata, 2018)
This study evaluated the concentration of Hg in the blood of the benthic fish species Geophagus brasiliensis captured from the Rio Grande and Billings Reservoir, which is located along the Upper Tiete River Basin (Sao Paulo, Brazil), to determine recent exposure. The relationship between blood and sediment Hg concentrations was evaluated. Sediment and fish blood samples were collected at six sampling sites during the rainy (January-March) and dry season (July-August) of 2009, and the rainy season (January) of 2010. Total Hg in blood and in sediments was determined by cold vapor atomic absorption spectrometry (CV AAS). The highest Hg concentrations in blood occurred in sampling sites located downstream from a chlor-alkali plant Weight and length of fish were marginally associated with concentrations of Hg in blood. According to international guidelines for sediment quality, Hg concentrations were higher than Probable Effect Level (PEL) (0.49 mu g/kg) in the final stretch of the Grande River and in the Billings Reservoir, while the remaining sites presented values between 0.06 and 0.35 mu g/kg. Pearson correlation analysis between the concentrations of Hg in blood and sediment was positive and significant (r=0.844, p<0.05), showing that quantification of Hg in blood can be an useful tool for biomonitoring, indicating recent exposure, as well as helping as an early warning indicator of environmental contamination.
Keywords: bioaccumulation; environmental quality; neotropical teleost; total mercury